Socialistic reorganization of advocacy: USSR' experience in the second decade of the XX century - Губар, Сергій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The legal grounds of advocacy activity are revealed. The influence of state social-economical policy on the forms of advocacy activity is been tracked. During NEP period the advocacy associations were founded of Provincial Councils of People's Courts, and after Provinces were dissolved - of district courts. There were self-governed organizations on self financing basis; their work was conducted in two forms - private cabinet or legal advice. NEP curtailing and private economy sector cutting necessitated the advocacy reorganization. The question of further advocacy activity's forms was brought up a point of all-people's discussion directed by the ruling Party. As a result the private cabinet practice was discontinued and transition to collective work was made. During the advocacy reorganization the advocacy associations' "purge" was conducted with the aim to fire people considered socially and ideologically aliens to the Bolshevik's regime. As a result the state influence in the advocacy activity was strengthened.